Legislación y moneda en la Hispania visigoda - Javier de Santiago Fernández (Mélanges de la Casa de Velázquez)
The main object of this paper is to conduct an analysis of legislative sources from the Visigothic era relating to coinage. This is a novel approach, proposing new angles and useful hypotheses both for research into legislative sources and for the history of coinage. The authors have conducted a detailed study of the different monetary references cited in the Liber Iudiciorum, interpreting their meaning and significance and assessing their value for a fuller understanding of the coinage. They have also analysed the only laws in the Liber relating directly to coinage, in particular those referring to fraud. Finally, they posit the probable existence of legislation intended to specify the characteristics of particular coinage issues, through mandata, from the central authority to the provincial authorities, which would have passed them on to the bodies responsible for the actual minting, presumably goldsmiths.